2008
DOI: 10.1158/0008-5472.can-08-0896
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Cannabinoid Receptor 1 Accelerates Intestinal Tumor Growth

Abstract: Although endocannabinoid signaling is important for certain aspects of gastrointestinal homeostasis, the role of the cannabinoid receptors (CB) in colorectal cancer has not been defined. Here we show that CB1 expression was silenced in human colorectal cancer due to methylation of the CB1 promoter. Our genetic and pharmacologic studies reveal that loss or inhibition of CB1 accelerated intestinal adenoma growth in Apc Min/+ mice whereas activation of CB1 attenuated intestinal tumor growth by inducing cell death… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
151
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(161 citation statements)
references
References 40 publications
8
151
2
Order By: Relevance
“…In thyroid, breast, glioma, and prostate cancer cells, Cnr1 agonists inhibited proliferation which could be abrogated by antagonists (18,(41)(42)(43). Moreover, conflicting results have been obtained in colorectal cancer where Cnr1 agonists can induce apoptosis and inhibit growth, whereas antagonist treatment can either accelerate or prevent precancerous lesion formation, depending on the animal model used (37,44,45). However, we could find no contribution of Cnr1 to PAX3-FOXO1-induced myoblast growth.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…In thyroid, breast, glioma, and prostate cancer cells, Cnr1 agonists inhibited proliferation which could be abrogated by antagonists (18,(41)(42)(43). Moreover, conflicting results have been obtained in colorectal cancer where Cnr1 agonists can induce apoptosis and inhibit growth, whereas antagonist treatment can either accelerate or prevent precancerous lesion formation, depending on the animal model used (37,44,45). However, we could find no contribution of Cnr1 to PAX3-FOXO1-induced myoblast growth.…”
Section: Discussioncontrasting
confidence: 67%
“…This increased invasive and metastatic capacity contribute to the poorer prognosis associated with ARMS (1-3). Because Cnr1 has been associated with cell migration and tumor invasiveness (19,20,(37)(38)(39), we wished to determine whether Cnr1 played a role in this PAX3-FOXO1-dependent phenotype.…”
Section: Cnr1 Upregulation Does Not Contribute To Proliferation Diffmentioning
confidence: 99%
“…Moreover, several studies confirmed proapoptotic and antiproliferative effects of cannabinoids in different cancer cells by mechanisms involving, for instance, de novo synthesis of ceramide (Galve-Roperh et al, 2000;Hinz et al, 2004) or activation of mitogen-activated protein kinases (GalveRoperh et al, 2000;Herrera et al, 2005). Furthermore, recent data support the hypothesis that cannabinoid receptors together with endogenously produced agonists contribute to an endogenous defense mechanism against tumorigenesis Ligresti et al, 2003;Di Marzo et al, 2004;Kishimoto et al, 2005;Wang et al, 2008).…”
mentioning
confidence: 87%
“…We have recently shown that activation of the CB1 receptor by the plant-derived cannabinoid, Δ 9 -tetrahydrocannabinol (THC) induces CB1-dependent apoptosis via inhibition of both RAS-MAPK/ERK and PI3K-AKT signalling cascades in colon cancer cells, (two key survival pathways frequently deregulated in colorectal cancer (13). Furthermore, activation of CB1 was recently reported to attenuate intestinal tumour growth in Apc(Min/ + ) mice suggesting that the endogenous cannabinoid system may represent a potential therapeutic target for prevention or treatment of colorectal cancer (14).…”
Section: Introductionmentioning
confidence: 99%